A Study to Assess the Personality of Supply Chain Managers and its Effect on Supply Chain Performance - Nazempour, Rayhaneh; Yang, Jianhua (International Journal of Social and Administrative Sciences, 2019)
Supply chain management (SCM) is a growing field where supply chain managers play an important role in the field of SCM. In this research, five factor model (FFM), e.g., extraversion (EPT), emotional stability (ESPT), agreeableness (APT), openness to experience (OPT), and conscientiousness (CPT) were assumed as the factors of Supply Chain Performance (SCP). Data were gathered from 150 supply chain managers (SCMG) and analysis assured that FFM has positive correlation with SCP in the Iranian SMEs. We also observed that some factor of FFM which are APT and OPT are closely associated to SCP whereas three factors of FFM, e.g., ESPT, CPT, and EPT has less positive correlation to SCP on present instant. This affirmed the higher positive connections of two factors of FFM, i.e., APT and OPT relatively than ESPT, CPT, and EPT, respectively. This research proposed certain implications and future research for future researchers and provided several suggestions for the policy makers.